Performance of maize (Zea mays) + field bean (Dolichos lablab) intercropping system under natural, organic and conventional farming practices - A H, KUMAR NAIK; GOUDRA, SHIVANAND; K, GOVINDA; A, ANANTHA RAMA; U, DIVYAJYOTHI; S, SUJATHA; M, PALLAVI (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out at Zonal Agricultural and Horticultural Research Station, Babbur Farm, Hiriyur, Chitradurga, Karnataka during rainy (kharif) season 2019, 2020, 2021 and 2022 to study the productivity and economics of maize (Zea mays L.) + field bean (Dolichos lablab L.) (4:2) intercropping system under different farming practices. The experiment was laid out in randomized complete block design (RCBD) with four farming practices as treatments, viz. T1, Natural farming (NF); T2, Organic farming (OF); T3, Recommended package of practices (RPP) and; T4, Farmer practices (FP) with five replications. Results revealed that the recommended package of practices (RPP) recorded a significantly higher maize grain yield (6045 kg/ha), seed yield of field bean (538 kg/ha), maize equivalent yield (9625 kg/ha). Cost of cultivation in different farming practices indicated the lowest labour cost incurred in organic farming (₹25405/ha) and material cost in natural farming (₹14576/ha) as compared to other farming practices. Among the farming practices, lowest cost of cultivation was observed under natural farming (₹45436/ha) as compared to other farming practices. The gross returns (₹166471/ha) and net returns (₹109428/ha) were again significantly higher in RPP over other farming practices.